1995
DOI: 10.1177/0310057x9502300217
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cryptantigen Exposure and Polyagglutinability: Management of Transfusion Therapy in a Patient with Sepsis and Colitis

Abstract: The diagnosis of microbial-induced T (Thomsen-Freidenreich) red blood cell (RBC) cryptantigen exposure and polyagglutinability and management of transfusion therapy for such patients poses a potential clinical problem. These phenomena are often not detectable by standard cross-matching techniques and may go unrecognized unless specific testing prompted by the clinical setting is performed. Infusion of standard plasma-containing blood products (a rich source of IgM anti-T) may cause intravascular haemolysis, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Purified albumin concentrates and highly purified coagulation factor concentrates contain essentially no IgM 70 . Similarly, only trace amounts of IgM are present in preparations of IVIG 76 . Thus, exposure to anti‐T with these products is usually not an issue.…”
Section: Transfusion Management Of T Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified albumin concentrates and highly purified coagulation factor concentrates contain essentially no IgM 70 . Similarly, only trace amounts of IgM are present in preparations of IVIG 76 . Thus, exposure to anti‐T with these products is usually not an issue.…”
Section: Transfusion Management Of T Activationmentioning
confidence: 99%
“…Some investigators have suggested that T‐activated RBCs that do not show in vitro polyagglutination with normal adult sera may not pose a hemolytic threat to the patient 28 . Screening plasma in advance with T‐activated reagent RBCs has also been proposed, 76 but human sera may show discordant anti‐T titers when tested with RBCs transformed with different microbes 1,79 …”
Section: Transfusion Management Of T Activationmentioning
confidence: 99%